Urinary proteome alterations in HER2 enriched breast cancer revealed by multipronged quantitative proteomics - Gajbhiye, Akshada; Dabhi, Raju; Taunk, Khushman; Vannuruswamy, Garikapati; RoyChoudhury, Sourav; Adhav, Ragini; Seal, Shubhendu; Mane, Anupama; Bayatigeri, Santhakumari; Santra, Manas K.; Chaudhury, Koel; Rapole, Srikanth (Proteomics, 2016)
Globally, breast cancer is the second most common cancer among women. Although biomarker discoveries through various proteomic approaches of tissue and serum samples have been studied in breast cancer, urinary proteome alterations in breast cancer are least studied. Urine being a noninvasive biofluid and a significant source of proteins, it has the potential in early diagnosis of breast cancer. This study used complementary quantitative gel-based and gel-free proteomic approaches to find a panel of urinary protein markers that could discriminate HER2 enriched (HE) subtype breast cancer from the healthy controls. A total of 183 differentially expressed proteins were identified using three complementary approaches, namely 2D-DIGE, iTRAQ, and sequential window acquisition of all theoretical mass spectra. The differentially expressed proteins were subjected to various bioinformatics analyses for deciphering the biological context of these proteins using protein analysis through evolutionary relationships, database for annotation, visualization and integrated discovery, and STRING. Multivariate statistical analysis was undertaken to identify the set of most significant proteins, which could discriminate HE breast cancer from healthy controls. Immunoblotting and MRM-based validation in a separate cohort testified a panel of 21 proteins such as zinc-alpha2-glycoprotein, A2GL, retinol-binding protein 4, annexin A1, SAP3, SRC8, gelsolin, kininogen 1, CO9, clusterin, ceruloplasmin, and alpha 1-antitrypsin could be a panel of candidate markers that could discriminate HE breast cancer from healthy controls.
Keywords: 2D-DIGE; Biomedicine; Breast cancer; HER2 enriched; SWATH; Urinary biomarkers